LEXICAL IMPACT FOR THE IDEOLOGY IN HEADLINE NEWS: INDONESIA SALT IMPORT ISSUE - Aniesa Haque Ayu; Nurul Chojimah; Esti Junining (Universitas Sebelas Maret, 2020)
This research focused on how the ideology can be revealed from the headline news which focus on its lexical choice that hide the meaning. This study used an online media news which published on Detik.com that has the headline Punya Garis Pantai Terpanjang di Dunia, Kok RI Impor Garam? As the mind object. This object also focused on its discourse as the mind media of analysis and the headline used as the point of view through the news. To analyse the object the researcher used critical discourse analysis by Van Dijk as the mind approach in analysing the discourse through the news and also supported in metafunction by Halliday which concern on ideological metafunction to help revealing the ideology.The study used qualitative as the design of analysis, it needed to describe the data. The aim of doing the research was to come up the ideology that hidden behind the headline of news. The issue was controversially and it would be the grand topic to be analysed. From the analysis known that the discourse of the news could build contradictive perspective between the headlines through the whole of discourse. That perspective came from the discourse which has been selected in its lexical and composing the pattern of sentences.